The Effects of Local Government Characteristics and Audit Opinion on the Performance of District and City Governments in Indonesia - Dewata, Evada; Jauhari, Hadi; Aprianti, Siska; Hijria, Eka Nurfa (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This study aims to examine the influence of district and city characteristics (fiscal decentralization ratio, dependency level on the central government, capital expenditure, age, regional status, population) and audit opinion on the performance of local and district government in Indonesia for the period of 2013-2015. Population of this study consists of all local government units of districts and cities in Indonesia for the years of 2013-2015. The purposive sampling method was used resulting in a total of 1,158 samples for three years period observations. The results of this study indicate that the variables of age area, population, and audit opinion have a positive effect on the performance of the studied Districts and Cities. Conversely, the dependency level on the central government has a negative effect on the performance of studied local governments. However, the ratio of fiscal decentralization, the capital expenditure, and the regional status have no effect on the performance of the local governments